Losers and losers: Some demographics of medical malpractice tort reforms - Andrew I. Friedson; Thomas J. Kniesner (Institute for the Study of Labor (IZA), 2011)
Our research examines individual differences in the effects of medical malpractice tort reforms on pre-trial settlement speed and settlement amounts by age and most likely settlement size. Findings of note include that, unlike previously assumed, both absolute and percentage losses from tort reform are small for infants in an asset value sense and that the prime-aged working population is the group most negatively affected by tort reform. Maximum entropy quantile regressions highlight the robustness of our conclusions and reveal that the settlement losses most informative for policy evaluation differ greatly from mean regression estimates.
urn:nbn:de:101:1-20110927496
Keywords: C21; I18; 330; medical malpractice; tort reform; Texas closed claims; damage caps; quantile regression; maximum entropy; Medizinische Behandlung; Haftung; Reform; Altersgruppe; Schuldrecht; Schiedsgerichtsbarkeit; Schiedsgerichtsbarkeit; USA